Effect of sintering temperature on the physical properties of Ba0.6Sr0.4TiO3 prepared by solid-state reaction - Rusiyanto, R.; Widodo, R. D.; Al-Janan, D. H.; Rohmah, K.; Siregar, J. P.; Nugroho, A.; Fitriyana, D. F. (Penerbit Universiti Malaysia Pahang, 2021)
Barium Strontium Titanate (BST) ceramic materials are widely used in electronic devices due to their stable operation at high temperatures, high tunability, low tangent loss, low DC leakage, and alterable curie temperatures. While pure BST materials are usually produced at high sintering temperatures (1250 °C), there are limited studies on the temperature and duration of the sintering process to produce pure BST, synthesised from micro or even nano-sized raw materials. This study aims to determine the effective sintering temperature for producing pure BST material using a mixture of raw materials with a mean particle size of 0.4 μm after milled for 58 hours. The BaCO3, SrCO3, and TiO2 materials as raw materials for Ba0.6Sr0.4TiO3 synthesis were milled for 58 hours to produce a homogeneous mixture with a mean particle size of 0.4 μm. Sintering was carried out in a temperature range of 500-1100 °C for 1 hour. This study investigates the impact of sintering temperature on the physical properties and the purity of Ba0.6Sr0.4TiO3 powder using the x-ray diffraction method. The results showed that the Ba0.6Sr0.4TiO3 phase was formed at a sintering temperature of 700 °C. Pure BST material was formed at the sintering temperature of 1000 °C with a crystallite size of 41 nm. Whereas at a higher sintering temperature (1100 °C), the pure BST material formed produced a larger crystallite, sized at 43 nm with cubic structure. The synthesis temperature and duration recorded in this research are lower than recorded in the BST material preparation using the solid-state method. The results of this study indicate that the sintering temperature greatly affects the purity, crystal system and crystallite size of the Ba0.6Sr0.4TiO3 material produced. The sintering temperature of 1100 °C produces Ba0.6Sr0.4TiO3 material with the best physical properties because it has a cubic-shaped crystal system and the largest crystal size.